Krótkoterminowa (nie)skuteczność algorytmu SuperMemo na przykładzie wybranej wiedzy historycznej - Piotrowski, Mikołaj (Kultura-Społeczeństwo-Edukacja, 2025)
The subject of the article is the SuperMemo algorithm, which forms the basis of various applications that aid memorization. It has been implemented, for instance, in the program Anki or in the application bearing the same name as the algorithm -SuperMemo. A two-stage experimental study of its short-term effectiveness was conducted among 282 pupils and students from Olsztyn, using selected historical knowledge as a basis. The results of the first stage suggest no advantage of the unmodified version of the algorithm over traditional learning methods, while the second stage indicates its effectiveness after introducing proprietary adjustments. This is manifested both in the objectively measured effectiveness of memorization and in the evaluations of individual algorithm versions declared by the participants. The difference obtained would hypothetically be even greater if the knowledge required to be mastered during the experiment were more extensive, which is a common scenario in school and university settings.